A Reconfigurable Ferromagnetic Input Device - and Taylor, Stuart; Butler, Alex; Villar, Nicolas; Izadi, Shahram (Proceeding of UIST 2009, 2009)
We present a novel hardware device based on ferromagnetic sensing, capable of detecting the presence, position and deformation of any ferrous object placed on or near its surface. These objects can include ball bearings, magnets, iron filings, and soft malleable bladders filled with ferrofluid. Our technology can be used to build reconfigurable input devices – where the physical form of the input device can be assembled using combinations of such ferrous objects. This allows users to rapidly construct new forms of input device, such as a trackball-style device based on a single large ball bearing, tangible mixers based on a collection of sliders and buttons with ferrous components, and multi-touch malleable surfaces using a ferrofluid bladder. We discuss the implementation of our technology, its strengths and limitations, and potential application scenarios.